School Principals’ Stress Profiles During COVID-19, Demands, and Resources - Upadyaya, Katja; Toyama, Hiroyuki; Salmela-Aro, Katariina (Frontiers in Psychology, 2021)
The present study examined latent profiles of school principals’ stress concerning students’, teachers’, parents’, and principals’ own ability to cope during the COVID-19 pandemic. In addition, the role of principals’ occupational well-being (job burnout and engagement), job psychological/social demands (workload, remote work stress, difficulty to detach from work, COVID-19 crisis, COVID-19 infections at school, impact of COVID-19 on future teaching), and resources (buoyancy, effective crisis leadership, social appreciation, successful transition to remote teaching), and occupational well-being (measured as job burnout and engagement) in predicting the latent profiles of stress sources was examined. The participants were 535 (59% women) school principals across Finland, who answered to a questionnaire concerning their sources of stress and occupational well-being during spring 2020. Three latent profiles were identified according to principals’ level of stress: high stress (41.4% of the school principals), altered stress (35.9%), and low stress (22.7%) profiles. Work burnout, workload, COVID-19 related concerns, and difficulty to detach from work increased the probability of principals belonging to the high or altered stress profile rather than to the low stress profile. Work engagement, buoyancy, and social appreciation increased the probability of principals belonging to the low rather than to the high or altered stress profile.